Silent Dialogues: The Reader’s Experience and Interpretation - Bidari Andaru Widhi; Syafira Mahfuzi Ardiati (CV. ULIL ALBAB CORP, 2024)
This article discusses silent reading for readers with the aim of investigating silent dialogues: the reader's experience and interpretation influence the reader. In addition, this article uses a qualitative open-ended question method with the aim of digging deeper information from the participants. Participants are randomly selected in order to get different results from each participant. The results obtained from silent reading, according to the participants, are very useful for the level of effectiveness in reading, especially studying texts that are difficult to understand. So, understanding the text with the silent reading method is very effective for learning to understand the text.